LAW APPLICABLE TO THE SUBSTANCE OF THE DISPUTE BEFORE AN ICSID ARBITRAL TRIBUNAL: ARTICLE 42(1) OF THE ICSID CONVENTION AND THE ROLE OF NATIONAL LAW - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Business transaction which represents a foreign investment is today most commonly regulated by three different layers of legal rules: provisions of an investment contract, rules of international law (treaties and rules of customary international law) and the legislation of the Host State. In the event of a dispute arising out of an investment, a tribunal working under the auspices of ICSID must determine the law applicable to the merits through the application of article 42(1) of the Convention. Although it is clear that one cannot fully comprehend all legal aspects of an investment dispute without the context of the Host State’s national legislation, there is a strong tendency in arbitral disputes of neglecting such municipal legal rules in favor of international law. The paper concentrates on the evolution in interpretations of the choice of law provision from the Convention in the practice of ICSID tribunals. It shows the way in which those interpretations have changed during the course of time, leading to the broadening of arbitrators’ freedom to decide on the applicable law. This trend resulted in constant widening of the scope of application of international law, contrary to the text of article 42(1) and intentions of the Convention’s makers. As a consequence, there is today almost no way in which a state could shield itself from the liability for the breach of the investor’s rights by invoking the fact that it acted in accordance with domestic legislation.